Benzodiazepine use in the population aged 18 to 40 years in the municipality of Bijelo Polje - Boskovic, Vasilije; Vlaovic Boskovic, Jelena; Mihaljevic, Olgica B; Djordjevic, Jelena; Tomovic, Filip; Babovic, Batric (PONS - medicinski časopis, 2023)
Objective: The aim of our study was to examine the pattern of benzodiazepines' use in young adults in the municipality of Bijelo Polje, Montenegro.Methods: The investigation was conducted as a cross-sectional study which involved 80 subjects of both gender aged between 18 and 40 years. The data were collected using self-administered survey questionnaire, consisted of 14 closed-ended questions related to sociodemographic characteristics and behavioural patterns with benzodiazepines' consumption.Results: More than half of study population confirmed the usage of benzodiazepines (55%). There were statistically significant differences in the duration of drug use so that the most frequent period was 1‒5 years (p= 0.025). Study participants claimed that they often used benzodiazepines optionally (43.18%), and in some stressful events (29.56%). The manner of drug supply varied significantly (p= 0.010). The majority of study population applied a drug dose of less than one milligram per day (22.72%), less than 2 milligrams per day in stressful circumstances (25%). The most common way of drug supplying was via prescription (36.36%) and taking it from family members (27.29%%). The analysis of the awareness of possible drug addiction indicated significant differences in attitudes of participants (p < 0.001). Conclusion: A high frequency of benzodiazepine use with a specific common pattern in consumption requires the improvement of health policy measures in the area of the drug abuse and possible development of addiction.
Keywords: abuse; benzodiazepines; drug addiction